Respuesta :

write out every grouping

(x-3)(x-3)(x-3)(x-3)*(x+6)(x+6)

and multiply

4x^2+3x+63

Answer:

3,3,3,3 ,-6, and -6.

Step-by-step explanation:

Given the polynomial function

f(x) = [tex](x-3)^4(x+6)^2[/tex]

To find the roots of given polynomial we put f(x)=0

[tex](x-3)^4(x+6)^2[/tex]=0

Then we put

[tex](x-3)^4=0[/tex]  and [tex](x+6)^2=0[/tex]

Now, we put each factor of (x-3 )equal to zero

x-3=0

x=3

x-3=0

x=3

x-3=0

x=3

x-3=0

x=3

Similarly , we put each factor of (x+6 ) equal to zero

Then we get

x+6=0

x=-6

x+6=0

x=-6

Multiplycity of 3=4

 Multiplicity of -6= 2.

Multiplicity of any number is defined as the number of repeatation of that number in polynomial function.

Therefore, the roots of given polynomial function are 3,3,3,3-6 and -6.